Електронна колориметрія – сучасний метод вимірювання концентрації речовин - Білецький, П. М. (ХНУРЕ, 2025)
This work is aimed at researching and improving colorimetric analysis tools for liquids and gases, in particular in medical laboratories. A device has been developed, the advantage of which is to expand the functionality of a digital sensor by adding the function of measuring the degree of light permeability of optical media. The proposed device includes several LEDs emitting in different spectral ranges, as well as a white LED. Three photodiodes with light filters and one more that perceives white light are used as receivers. The output signal of the photodiodes is amplified and converted into digital form.
Keywords: електронна колориметрія; вимірювання концентрації речовин